Improving the Health Independence of Muaragembong Community through the Utilization of Family Medicinal Plants (TOGA) - Yulius Evan Christian; Dini Permata Sari (Pharmacy Action Journal, 2025)
AbstractThe utilization of Family Medicinal Plants (TOGA) has become a focus in efforts to improve public health through natural and independent means. This community service activity was conducted in Muaragembong, aiming to increase the community's knowledge about the benefits of TOGA and how to use it in daily life. The identified issue was the lack of understanding and skills within the community to utilize the medicinal plants available around them. The method employed in this service activity was a participatory-based extension, followed by hands-on training on how to plant, maintain, and process TOGA into beneficial herbal products. The results obtained showed a significant increase in participants' knowledge, from 33,21% in the pre-test to 64,64% in the post-test. The majority of participants now have a better understanding of the health benefits of various TOGA plants, such as turmeric, ginger, and moringa. This activity also had a positive impact on economic empowerment, with many participants planning to plant TOGA in their yards and share the knowledge with others. The importance of this result is to introduce the community to an alternative natural treatment that can support independent health, while also creating opportunities for economic empowerment through the cultivation of medicinal plants.Keywords: Family Medicinal Plants; Community empowerment; Natural health; Sustainable economy; TOGA